(untitled) (Scientific journal of the Fergana State University, 2024)
Dam-prone lakes are widespread in mountainous areas. In many cases, their occurrence is associated with the formation of natural dams; as a result of physical and geographical processes, river valleys are blocked by landslides, landslides and landslides of various sizes. Such dams, depending on the conditions of their formation, cause the formation of landslide-tectonic, glacial, moraine, landslide and avalanche lakes. Dammed lakes accumulate large volumes of water and are one of the main sources of natural hazards such as catastrophic floods.To this end, today dam lakes attract the attention of specialists as a special object of study and require research based on a special scientific approach. This is of great scientific and practical importance when developing an action plan aimed at reducing the risk of dammed lakes, preventing floods that may occur due to dam breaks for various reasons, or at least reducing their damage. In this article describes the geographical distribution of dam lakes in the river basins of Central Asia, methods for assessing flood risk, as well as the grouping of lakes according to the degree of change in hazard category.